Praxis-Beispiel. Velo-Hauslieferdienst. - (:unkn) unknown (My University, 2013)
http://www.mobilservice.ch
Keywords: Fahrradverkehr; Individualverkehr; Einkauf; Fahrradnutzung; Fahrradbenutzung; Lastenrad; Transportmittel; Praxisbeispiel